The Effect Of Digital Literature Ability On Academic Resilience Through Student Self-Efficiency - Makmur Solahudin; Heru Sujiarto; Achamd Mudrikah; Usep Kosasih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The rapid development of digital technology in the current era of the industrial revolution 4.0, has made digital technology the basis or basis in human life, including in the field of education in Indonesia. This study aims to analyze the effect of digital literacy ability on students' academic resilience both directly and through student self-efficacy in the Depok City area. This study uses a quantitative approach with a path analysis approach. The population is all students studying in Depok City with a sample of 410 students taken by random sampling. The results showed that the direct influence of digital literacy ability on academic resilience was 0.220, the value of sig. 0.000, the effect of self-efficacy on academic resilience is 0.448, sig. 0.000. the indirect effect of digital literacy ability on academic resilience through self-efficacy is 0.099. The conclusion is that digital literacy ability have a direct positive and significant effect on student academic resilience, the role of self-efficacy in mediating the effect of digital literacy ability on students’ academic resilience is included in the category of partial mediation.